Smoking in pregnancy is a key factor for sudden infant death among Māori. (17th July 2018) - MacFarlane, M; Thompson, J M D; Zuccollo, J; McDonald, G; Elder, D; Stewart, A W; Lawton, B; Percival, T; Baker, N; Schlaud, M; Fleming, P; Taylor, B; et al.
Abstract: Aim: To examine the sudden unexpected death in infancy (SUDI) disparity between Māori and non‐Māori in New Zealand. Methods: A nationwide prospective case–control study ran from March 2012 to February 2015. Exposure to established SUDI risk factors was analysed to investigate the disparity experienced by Māori. Infant ethnicity was based on mother's ethnicity. Māori ethnicity was prioritised. Non‐Māori includes Pacific, Asian, NZ European and Other. Results: There were 137 cases and 649 controls. The Māori SUDI rate was 1.41/1000 live births compared to 0.53/1000 for non‐Māori. Parents/caregivers of 132 cases (96%) and 258 controls (40%) were interviewed. Smoking in pregnancy was associated with an equally increased SUDI risk for Māori (adjusted OR = 8.11, 95% CI = 2.64, 24.93) and non‐Māori (aOR = 5.09, 95% CI = 1.79, 14.47), as was bed‐sharing (aOR = 3.66, 95% CI = 1.49, 9.00 vs aOR = 11.20, 95% CI = 3.46, 36.29). Bed‐sharing prevalence was similar; however, more Māori controls smoked during pregnancy (46.7%) than non‐Māori (22.8%). The main contributor relating to increased SUDI risk for Māori/non‐Māori infants is the combination of smoking in pregnancy and bed sharing. Conclusion: The association between known SUDI risk factors, including bed sharing and/or smoking in pregnancy and SUDI risk, is the same regardless of ethnicity. Māori infants are exposed more frequently to both behaviours because of the higher Māori smoking rate. Abstract :